Comparison of histopathological findings with clinical response among patients undergoing consecutive renal biopsy for lupus nephritis in 2008-2021 (2023)
Introduction: Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disease involving several systems and has a high occurrence in areas such as the kidney, central nervous system, and vascular and serous structures. Furthermore, SLE poses a significant and increased risk of infections as well as an increase in morbidity and mortality. This increase is due to the presence of risk factors such as the use of corticosteroids, immunosuppressive drugs, and cytotoxic agents; changes in renal function; leukopenia, hypoalbuminemia; and alterations in both renal function and immunological profile (complement, anti-DNA). Renal biopsy (RB) is a safe method for obtaining renal tissue for the diagnosis and prognosis of SLE. Although complications, such as hemorrhage, are rare, if they do occur, they usually do so during the first 8-24 hours of the procedure. This diagnostic method is the best tool to diagnose lupus nephritis. Hence, we conducted a study to determine the histological changes in patients with lupus nephritis who were evaluated with consecutive biopsies from 2008 to 2021. Materials and Methods: An observational, analytical, and retrospective study was conducted using information collected from the RB database. Data on SLE and/or lupus nephritis recorded in this database by Clínica de la Costa uninterruptedly from 2008 to 2021. Patients with a diagnosis of SLE were selected based on at least four diagnostic criteria of the American College of Rheumatology. Those who had undergone renal puncture biopsy according to the consensus criteria of the group of systemic autoimmune diseases of the Spanish Society of Nephrology were selected. Results: A significant increase was observed in chronicity rates. Conclusion: Consecutive renal biopsy in LN allows early identification of the progress of the histopathological lesion. In this study, 30.7% of class III patients in their first renal biopsy presented histologicalprogress toward class IV in their consecutive biopsy.